Predicting shrinkage in semi-crystalline injection mouldings : the influence of pressure - Pontes, A. J. (2006)
In this study, the as-moulded shrinkage and pressure data are obtained experimentally and compared with numerical simulations. The mouldings were produced in polypropylene (PP). The effect of pressure on viscosity in the predicted pressure evolution was analyzed and also its influence on the shrinkage. The results show that the rise of holding pressure determines the reduction of the shrinkage. Also, it was observed that the pressure predictions are qualitatively in good agreement with the experimental data. However noticeable quantitative discrepancies can be observed when the effect of pressure on viscosity is not considered. If the effect of pressure on the melt viscosity is considered the deviation between predicted and the experimental pressure evolution is substantially reduced.